2018
DOI: 10.3390/ijms19061592
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Depression from the Microbiota–Gut–Brain Axis

Abstract: Major depression is one of the leading causes of disability, morbidity, and mortality worldwide. The brain–gut axis functions are disturbed, revealed by a dysfunction of the brain, immune system, endocrine system, and gut. Traditional depression treatments all target the brain, with different drugs and/or psychotherapy. Unfortunately, most of the patients have never received any treatment. Studies indicate that gut microbiota could be a direct cause for the disorder. Abnormal microbiota and the microbiota–gut–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
164
0
37

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(209 citation statements)
references
References 160 publications
(258 reference statements)
8
164
0
37
Order By: Relevance
“…IBS patients who also have MDD are less responsive to psychotherapy and antidepressants (Whorwell et al, 1987;Drossman et al, 2000), hence maintaining the makeup of gut microbiota through prebiotics and probiotics appears to be an ideal treatment for depression in epilepsy. In support of this notion, research has indicated that depression, anxiety, and panic attacks (Schnorr and Bachner, 2016;Liang et al, 2018a) may be from abnormal gut microbiota. The robust link between depressive symptoms to the gut microbiota can be seen in research conducted whereby the GF or microbiota-depleted animals presented defective brain development and abnormal mental growth (Luczynski et al, 2016;Chen et al, 2017), indicating that both neuroplasticity and myelin plasticity is regulated by the gut microbiota.…”
Section: Gut Microbiota-depression In Epilepsymentioning
confidence: 98%
“…IBS patients who also have MDD are less responsive to psychotherapy and antidepressants (Whorwell et al, 1987;Drossman et al, 2000), hence maintaining the makeup of gut microbiota through prebiotics and probiotics appears to be an ideal treatment for depression in epilepsy. In support of this notion, research has indicated that depression, anxiety, and panic attacks (Schnorr and Bachner, 2016;Liang et al, 2018a) may be from abnormal gut microbiota. The robust link between depressive symptoms to the gut microbiota can be seen in research conducted whereby the GF or microbiota-depleted animals presented defective brain development and abnormal mental growth (Luczynski et al, 2016;Chen et al, 2017), indicating that both neuroplasticity and myelin plasticity is regulated by the gut microbiota.…”
Section: Gut Microbiota-depression In Epilepsymentioning
confidence: 98%
“…10 It has been shown that Bacteroides genus in patients diagnosed with MDD was increased, while the Lachnospiraceae genus was decreased. Consequently, intestinal microbiome dysbiosis has been associated with many mental disorders including depression.…”
Section: Intestinal Microbiota On Mitochondriamentioning
confidence: 99%
“…Contrastingly, other microbiota have been shown to exert the opposite effect. This may be significant, given that neuroinflammation has been identified as being key in the pathogenesis of multiple psychiatric conditions including both anxiety disorder and major depressive disorders (MDDs) 9–14…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan (TRP), a precursor of the neurotransmitter serotonin, is one such example 16. It is possible that cross-talk mechanisms may form part of the pathophysiology of anxiety disorders and/or depression, which highlights them as potentially utilisable therapeutic avenues for treating these conditions 11 16. Finally, it must be highlighted that the mechanisms by which GBA interactions are enacted suggest that the effects microbiota have on their host physiologically, or during pathophysiological states, may be detectable within the host’s biochemical profile.…”
Section: Introductionmentioning
confidence: 99%